Evidence of Sex-related Differences in Cytochrome P450 2C19 and 3A4 Mediated Metabolism of Omeprazole: Observations in an Understudied Population in South-East Anatolia in Turkey - S. Aynacoglu, Ahmet; Z. Ongen, Hatice (Current Pharmacogenomics and Personalized Medicine, 2013)
Sex-dependent and population differences in the activities of cytochrome P450 enzymes affect the metabolism of many xenobiotics, including drugs. The proton pump inhibitor omeprazole is widely prescribed in many countries that call for population studies of its disposition. Omeprazole is metabolized by CYP2C19 and CYP3A4, resulting in the formation of 5-hydroxyomeprazole and omeprazole sulfone, respectively. This study examined the sex-differences in CYP2C19-, and CYP3A4-mediated metabolism of omeprazole in an understudied population in Turkey. Data were obtained from 107 healthy unrelated subjects (51 females and 56 males; heterozygous and homozygous extensive metabolizers (EMs) in regard to CYP2C19) from a recent study on the relationship between CYP2C19 genotype and phenotype, using a single oral dose of 60 mg R,S-omeprazole. The differences in plasma concentrations of racemic omeprazole, its R- and S-enantiomers, 5-hydroxyomeprazole, and omeprazole sulfone as well as the metabolic ratios of omeprazole and its enantiomers were compared between females and males. We also examined the parameters mentioned above in homozygous EM (CYP2C19*1/*1) subjects (n=90). No significant differences of metabolic ratios (MRs) (omeprazole/5-hydroxyomeprazole (O/OHO), omeprazole/omeprazole sulfone (O/OS), omeprazole plus 5-hydroxyomeprazole/ omeprazole sulfone (O+OHO/OS), omeprazole plus omeprazole sulfone/5-hydroxyomeprazole (O+OS/OHO), and the same ratios for its S-, and R- enantiomers) were found between females and males in the homozygous EM group, except a trend for difference of the O+OS/OHO (P=0.061), RO+OS/OHO (P=0.047) and SO+OS/OHO (P=0.072) MRs, which was higher in females. In the heterozygous plus homozygous EMs with regard to CYP2C19, the MR of O+OS/OHO (P=0.059) was borderline higher in females, while the O+OHO/OS (P=0.009) MR was higher in males. Similar results were found for MRs of R-, and S-omeprazole (RO+OS/OHO, P=0.040; SO+OS/OHO P=0.018; RO+OHO/OS, P=0.005; SO+OHO/OS, P=0.007). There are sex-related differences in the MRs of omeprazole and its R-, and S- enantiomers, also suggesting that females have a higher CYP3A4, but a slightly lower CYP2C19 activity compared to males in healthy Turkish subjects.
Keywords: CYP3A4